2009
DOI: 10.1111/j.1600-0579.2009.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rural outplacement programme for dental undergraduates: students’ perceptions

Abstract: Overall feedback indicated that the students found it a very positive and enjoyable experience. It provided an opportunity to appreciate cultural safety and understand the specific oral health needs of indigenous Australians. The key benefit of such a programme to the community is the increased likelihood of attracting new dental graduates to rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(125 citation statements)
references
References 27 publications
10
115
0
Order By: Relevance
“…Six of the eleven articles were from Australia, two from South Africa and one from the United States, India and Thailand …”
Section: Resultsmentioning
confidence: 99%
“…Six of the eleven articles were from Australia, two from South Africa and one from the United States, India and Thailand …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Abuzar et al reported that clinical rotations in rural areas provided “worthwhile” and “enjoyable” experiences for dental students. These experiences also helped dental students appreciate and understand the specific oral health needs of underserved populations 36. Aside from the increase of “rural spirit” in dental students, Mashabi and Mascarenhas37 and Formicola and Bailit38 suggested that clinical rotations in rural areas had important benefits in increasing basic skills, self-confidence, and speed in dental practice 37,38.…”
Section: Discussionmentioning
confidence: 99%
“…An eligible Aboriginal health placement experience was defined as a field trip, clinical placement or public/community health placement, of at least one week duration, that involved interaction with Aboriginal people. The eligibility criteria are consistent with the Aboriginal health placements studied in different health professions . Interactions within the context of lectures, tutorials, or similar were not classified as ‘placement’.…”
Section: Methodsmentioning
confidence: 99%
“…Cultural competence, defined as ‘a set of attitudes, skills, behaviours, and policies that enable organisations and staff to work effectively in cross‐cultural situations’, has been identified as a competency standard for the dietetic workforce . Research in other health professions including medical, nursing, dental and pharmacy, indicates that university Aboriginal health placements increase cultural knowledge, positive attitudes towards Aboriginal people, and perceived confidence and preparedness in working with Aboriginal people . Little is known about whether Aboriginal health placements positively influence the attitudes, skills and behaviours of dietetic graduates and how this occurs.…”
Section: Introductionmentioning
confidence: 99%